The Use of Mind Map Technique to Improve Study Group Students' Skill in Writing Descriptive Text - Kadek Diana Arista (Journal of Educational Study, 2021)
This study was conducted to improve the study group students’ skill in writing descriptive text using mind map technique. The subjects of the study were 9 students in Dana Punia Orphanage Singaraja. The data obtained was descriptively analyzed. The mean score of the pre-test was 54.5%, which was categorized as being poor to fulfill the students’ minimum standard score. After the treatment was conducted, the mean score of the students increased to 69.6% in the first cycle, and then increased to 75.3% after conducting cycle 2. The result of the study showed that the students’ achievement in writing descriptive text improved, it meant that the Mind Map technique was a very effective technique to be applied in writing descriptive text. This study is expected could be used as a reference for other researchers in conducting further study related to the teaching of writing in school, also as a comparison study for conducting technique in teaching writing especially using mind map Technique.